A conservative approach to Aspergillus sinusitis - Babayeva, Fidan; Saruhan, Nesrin; Oz, Yasemin; Onur Orhan, Ekim (Annals of Medical Research, 2021)
None
Keywords: Aspergillus; maxillary sinus; OrthoMTA; pathology; retreatment